TLC-BIOAUTOGRAPHY GUIDED SCREENING OF THE METHANOLIC EXTRACT OF RICINUS COMMUNIS - NATHANIEL SANDAM; PONNAMMA SU (International Journal of Pharma and Bio Sciences, 2015)
New medicines are required to treat various kinds of bacterial diseases since bacteria tend to develop characteristics like drug resistance resulting in the ineffectiveness of the presently used drugs. Therefore, there is a need to exploit the antimicrobial activities of plants for the treatment of infections and to treat infections caused by drug resistant bacteria as an alternative.¹The antimicrobial activity of Ricinus communis was investigated by TLC-Bioautography. Preliminary screening of the methanolic extracts of Ricinus communis showed that the extract contains alkaloids, saponins, oils and fats, phenols, flavanoids, tannins and glycosides. From among the various solvent systems tested, the 3 solvent system of Chloroform: Petroleum ether: Ethyl acetate in the ratio 8:2:2 was found to be the best as it resolved the methanolic extract into 8 good fractions. Among the 8 fractions, 4 were found to be antimicrobial by TLC- bioautography technique. The active fraction corresponding to Rf value 0.2750 showed distinct inhibitory zones against both Klebsiella pneumoniae (MTCC 3384) and Pseudomonas aeruginosa (PC 002) ². GC-MS analysis of this fraction revealed fatty acids as the major component. Our work has shown that the fraction corresponding to Rf value 0.2750 has potential to be used as an antimicrobial agent against Klebsiella pneumoniae and Pseudomonas aeruginosa.